Determinants of patients' satisfaction and trust toward healthcare service environment in general practice clinics - Ai, Yun; Rahman, Muhammad Khalilur; Newaz, Md. Shah; Gazi, Md. Abu Issa; Rahaman, Md. Atikur; Mamun, Abdullah Al; Chen, Xia (Frontiers in Psychology, 2022)
This study has aimed to examine the healthcare service environment, patient’s experience and responses towards healthcare services in private general practice (GP) clinics. Self-administered questionnaires employ for collecting data from 367 respondents with prior experiences visiting the general practice clinics in Malaysia. SmartPLS statistical tool uses to test the underlying hypotheses. The results reveal that ambience, service delivery, interior decor, and cleanliness have a significant influence on patient’s trust and satisfaction while the exterior design is neither associated with satisfaction nor trust. Patient’s satisfaction and trust have a higher significant effect on their repatronage intention, willingness to pay premium healthcare services, and word of mouth for healthcare services. In practice, both the service delivery and ambience features of the healthcare services environment might be optimized by GP clinics. This research will render significant insights from patients’ perspective towards the GP clinics’ healthcare services environment.